2022
DOI: 10.3389/fcimb.2022.935723
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota remodeling: A promising therapeutic strategy to confront hyperuricemia and gout

Abstract: The incidence of hyperuricemia (HUA) and gout continuously increases and has become a major public health problem. The gut microbiota, which colonizes the human intestine, has a mutually beneficial and symbiotic relationship with the host and plays a vital role in the host’s metabolism and immune regulation. Structural changes or imbalance in the gut microbiota could cause metabolic disorders and participate in the synthesis of purine-metabolizing enzymes and the release of inflammatory cytokines, which is clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 132 publications
1
29
1
Order By: Relevance
“…In the hindgut of pregnant goats, we detected a high abundance of adenine and purine metabolites, mainly deoxyadenosine, 2′-deoxyinosine, and 5′-deoxyadenosine, which were negatively correlated with the abundance of the genus Family_XIII_AD3011_group . Previous studies have shown that intestinal microbiota can be involved in purine metabolism in the body, and in patients with high uric acidity, the abundance of Bacteroides caccae and Bacteroides xylanisolvens was significantly increased, and the levels of Prevotella spp, Ruminococcus spp, and Lactobacillus spp were decreased ( 33 ). Escherichia coli , Lactobacillus , and Pseudomonas can secrete xanthine dehydrogenase, an enzyme in the oxidative metabolism of purines, responsible for the conversion of xanthine into uric acid ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the hindgut of pregnant goats, we detected a high abundance of adenine and purine metabolites, mainly deoxyadenosine, 2′-deoxyinosine, and 5′-deoxyadenosine, which were negatively correlated with the abundance of the genus Family_XIII_AD3011_group . Previous studies have shown that intestinal microbiota can be involved in purine metabolism in the body, and in patients with high uric acidity, the abundance of Bacteroides caccae and Bacteroides xylanisolvens was significantly increased, and the levels of Prevotella spp, Ruminococcus spp, and Lactobacillus spp were decreased ( 33 ). Escherichia coli , Lactobacillus , and Pseudomonas can secrete xanthine dehydrogenase, an enzyme in the oxidative metabolism of purines, responsible for the conversion of xanthine into uric acid ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have found a close association between intestinal flora and hyperuricemia. It was found that HUA mice and normal mice have significantly different intestinal flora composition and structure [ 59 ]. This situation was also observed during our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the changed gut microbes in patients with PDC were mainly associated with carbohydrate and amino acid metabolism, mineral absorption, lipopolysaccharide biosynthesis, primary bile acid biosynthesis, and so on. The altered gut microbial composition and function correspond to the clinical findings of HUA [ 57 ]. Therefore, the metabolic characteristics of people with PDC or DHC may be the reasons underlying the pathology of HUA.…”
Section: Discussionmentioning
confidence: 99%